2022
DOI: 10.1186/s12871-021-01531-2
|View full text |Cite
|
Sign up to set email alerts
|

Complete opioid transition to sublingual Buprenorphine after abdominal surgery is associated with significant reductions in opioid requirements, but not reduction in hospital length of stay: a retrospective cohort study

Abstract: Background The use of sublingual buprenorphine (SLBup) for acute pain after major abdominal surgery may offer the potential advantages of unique analgesic properties and more reliable absorption during resolving ileus. We hypothesized that complete opioid transition to SLBup rather than oral oxycodone (OOxy) in the early postoperative period after major abdominal surgery would reduce hospital length of stay, and acute pain and total OMEDD (Oral Morphine Equivalent Daily Dose) requirements in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Transition from parenteral to sublingual buprenorphine, compared to oxycodone, has been associated with significantly lower opioid use and pain scores. 25 Substituting oxycodone use with tapentadol has been supported by studies concluding equivalence of analgesia and a more favourable side-effect profile for tapentadol. 26,27 It has been recently reported that tapentadol has replaced oxycodone and tramadol to become the most frequently prescribed oral opioid prescribed in an Australian local health district.…”
Section: Discussionmentioning
confidence: 99%
“…Transition from parenteral to sublingual buprenorphine, compared to oxycodone, has been associated with significantly lower opioid use and pain scores. 25 Substituting oxycodone use with tapentadol has been supported by studies concluding equivalence of analgesia and a more favourable side-effect profile for tapentadol. 26,27 It has been recently reported that tapentadol has replaced oxycodone and tramadol to become the most frequently prescribed oral opioid prescribed in an Australian local health district.…”
Section: Discussionmentioning
confidence: 99%